Studi komperatif terhadap seberapa paham masyarakat gen z terhadap bank syariah - Rabbaniyyah, Aisyah (Maliki Interdisciplinary Journal, 2025)
This study aims to compare the level of public understanding of Generation Z towards Islamic banking in Indonesia. The background of this study is the gap between the level of conventional and Islamic financial literacy, even though Indonesia has a large Muslim population. This study used interview and documentation methods to collect data from representatives of both generations. The results show that Generation Z is more familiar with traditional banking products such as Murabahah and Wadi'ah. The conclusion of this study is that Islamic banks need to design different educational strategies for both generations, with a focus on risk management and the integration of ethical-digital values for Gen Z. This study also highlights the importance of digital innovation in attracting Generation Z's interest in Islamic banking.